Zeatin–auxin synergy and growing media optimization enhanced micropropagation, acclimatization, and antioxidant properties of ‘Bentong’ ginger (Zingiber officinale Roscoe) - Ahmad Zahid, Nisar; Jaafar, Hawa Z.E.; Hakiman, Mansor (Elsevier Ltd, 2025)
‘Bentong’ ginger (Zingiber officinale Roscoe) is a medicinally and economically important ginger cultivar in Malaysia. However, its conventional propagation via rhizomes is limited by low multiplication rates and a high risk of disease transmission. This study aimed to develop an efficient micropropagation protocol by optimizing the synergistic application of zeatin and auxins. Murashige and Skoog (MS) medium supplemented with 10 μM zeatin and 2.5 μM 1-naphthaleneacetic acid (NAA) significantly enhanced shoot multiplication (6.72 shoots per explant) and overall in vitro shoot development. Furthermore, the effects of different growing media on ex vitro acclimatization were evaluated. Plantlets grown in a 1:1:1 mixture of soil, coco peat, and vermiculite exhibited the highest survival rate (94.79 %) and superior vegetative and physiological performance, followed closely by a mixture of soil, peat moss, and vermiculite (93.75 % survival). Phytochemical analyses revealed no significant differences in total polyphenols content or antioxidant activities, assessed via 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging and iron-chelating assays, between rhizomes of micropropagated and conventionally propagated plants. These findings highlight the potential of zeatin–auxin synergy and optimized acclimatization media to efficiently produce disease-free, true-to-type ‘Bentong’ ginger planting materials.